Report from the World Health Organization's Product Development for Vaccines Advisory Committee (PDVAC) meeting, Geneva, 7–9th Sep 2015. Issue 26 (3rd June 2016) - Giersing, Birgitte K.; Modjarrad, Kayvon; Kaslow, David C.; Moorthy, Vasee S.; ,; ,; Bavdekar, Ashish; Cichutek, Klaus; Cravioto, Alejandro; Fritzell, Bernard; Graham, Barney S.; Karron, Ruth; et al.
Highlights: The RTS, S Plasmodium falciparum malaria vaccine has received a positive regulatory assessment by EMA. The CYD-TDV dengue vaccine has been licensed in some middle-income countries. A Phase 3 HIV vaccine trial is due to be initiated in South Africa during 2016–2017. The RSV vaccine pipeline is in Phase III clinical development and may reach the licensure submission stage within 4 years. Group B streptococcal vaccine development is advancing, as is the maternal immunisation agenda. Abstract: There are more vaccines in development, against a greater number of pathogens, than ever before. A challenge with this exceptional level of activity and investment is how to select and resource the most promising approaches to have the most significant impact on public health. The WHO Product Development for Vaccines Advisory Committee (PDVAC) was established in 2014 to provide strategic advice and recommendations to WHO for vaccines in clinical development that could have a significant impact on public health in low and middle income countries. On 7–9th September 2015, PDVAC was convened for the second time, when the committee reviewed vaccine developments in 24 disease areas. This report summarises the key recommendations from that consultation.